2023
DOI: 10.32607/actanaturae.11857
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of Transepidemal and Intradermal Immunization of Mice with the Vacinia Virus

Abstract: The spread of the monkeypox virus infection among humans in many countries outside of Africa, which started in 2022, is now drawing the attention of the medical and scientific communities to the fact that immunization against this infection is sorely needed. According to current guidelines, immunization of people with the first-generation smallpox vaccine based on the vaccinia virus (VACV) LIVP strain, which is licensed in Russia, should be performed via transepidermal inoculation (skin scarification, s.s.). H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Numerous studies have previously demonstrated that s.s. immunization with second-and fourth-generation VACVbased vaccines at doses of at least 10 5 -10 6 pfu fully protected mice against repeated lethal orthopoxvirus infection (Melamed et al, 2007;Jacobs et al, 2009;Shchelkunov et al, 2022a). * Statistically significant differences with p < 0.05.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have previously demonstrated that s.s. immunization with second-and fourth-generation VACVbased vaccines at doses of at least 10 5 -10 6 pfu fully protected mice against repeated lethal orthopoxvirus infection (Melamed et al, 2007;Jacobs et al, 2009;Shchelkunov et al, 2022a). * Statistically significant differences with p < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of i.d. injection, 20 µL of viral material (10 4 pfu) or normal saline (control group) was inoculated according to the procedure described earlier (Shchelkunov et al, 2022a). For s.s. immunization, 10 skin incisions were made using a 26G needle (0.45 × 16 mm) within the uppermost layer of epidermis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited MVA-BN vaccine supply led to US Food and Drug Administration recommendations to deliver an alternative regimen of one-fifth of the dose intradermally (ID) instead of a full dose subcutaneously (SC) (12). ID MVA immunization has been studied in mice, but little direct protection data are available for ID MVA vaccination against mpox in humans (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%